Weaving Narrative : Clothing in Twelfth-Century French Romance - Wright, Monica L., 1968- (Book collections on Project MUSE., 2009)
"Analyzes the relationship between twelfth-century French material culture, especially with regard to attire and personal adornment, and the compositional and narrative techniques used in the emerging genre of courtly verse romance"--Provided by publisher.